2020
DOI: 10.1002/anie.201916538
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Reconstruction of a Hierarchical Sn‐Cu/SnOxCore/Shell Catalyst for High‐Performance CO2Electroreduction

Abstract: The electrochemical CO2 reduction reaction (CO2RR) to give C1 (formate and CO) products is one of the most techno‐economically achievable strategies for alleviating CO2 emissions. Now, it is demonstrated that the SnOx shell in Sn2.7Cu catalyst with a hierarchical Sn‐Cu core can be reconstructed in situ under cathodic potentials of CO2RR. The resulting Sn2.7Cu catalyst achieves a high current density of 406.7±14.4 mA cm−2 with C1 Faradaic efficiency of 98.0±0.9 % at −0.70 V vs. RHE, and remains stable at 243.1±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
129
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(148 citation statements)
references
References 57 publications
2
129
0
Order By: Relevance
“…Up to now, a variety of catalysts, such as metals [14,15] , metal oxides [16] , metal sulfides [17] , carbon-based materials [18,19] , metal organic frameworks (MOFs) [20] , single atoms [21] , and molecular catalysts [22] , have been exploited. Ring-packed molecules with rigid plane like porphyrins (PP) and phthalocyanines (Pc) enable electrons transfer from PP/Pc to metal-center sites to tune the electronic structure of active sites due to their special πconjugation structure.…”
mentioning
confidence: 99%
“…Up to now, a variety of catalysts, such as metals [14,15] , metal oxides [16] , metal sulfides [17] , carbon-based materials [18,19] , metal organic frameworks (MOFs) [20] , single atoms [21] , and molecular catalysts [22] , have been exploited. Ring-packed molecules with rigid plane like porphyrins (PP) and phthalocyanines (Pc) enable electrons transfer from PP/Pc to metal-center sites to tune the electronic structure of active sites due to their special πconjugation structure.…”
mentioning
confidence: 99%
“…A facile one-step electrodeposition technique by using hydrogen bubbles as a dynamic template was reported by Ye et al [247] for the fabrication of 3D hierarchical SnOx@Sn-Cu/Sn core-shell catalysts supported on Cu foam. They demonstrated that the SnO x shell with a hierarchical Sn-Cu/Sn core can be reconstructed in situ under cathodic potentials of CO 2 RR.…”
Section: Cathode With Metal-based Catalystsmentioning
confidence: 99%
“…The calculation of catalyst intrinsic activity is of great importance. This is affordable in the case of electrocatalysts by the calculation of the electrochemically active surface area (ECSA), [69,70] or in case of metal catalysts by calculation of the turnover frequency (TOF). In our case, as the main catalyst is a metal oxide phase, a TOF may be calculated based on the specific number of exposed Co 3 + atoms.…”
Section: Composite Catalysts Without Aumentioning
confidence: 99%